Bioinspired Stereoselective Total Synthesis of the Caged Sesquiterpenoid Daphnepapytone A - Yan Zhang (8098) (2025)
The first total synthesis of the novel caged sesquiterpenoid daphnepapytone A is disclosed. Key reactions include a Pauson–Khand cycloaddition to provide oleodaphone, a bioinspired photoinduced [2 + 2] cycloaddition to forge the cyclobutane-containing caged skeleton, and a C–H oxidation and reduction protocol to generate daphnepapytone A. Finally, the 17-step synthetic sequence is shortened to 4 steps in protecting group-free and exclusively stereoselective fashion.